INFORMATIVE ENERGY EXCHANGE OF PERIPHERAL LYMPHOCYTE BLOOD MITOCHONDRIA IN CHILDREN WITH CHRONIC CONSTIPATION - G.F. Semenova; E.V. Komarova; A.S. Potapov; A.V. Petrova; V.M. Shishchenko; S.V. Petrichuk ("Paediatrician" Publishers LLC, 2007)
The article discusses the study of cell metabolism condition in chronic constipation children based on the activities of the two mitochondrion enzymes, succinate dehydrogenate and glycerophosphate dehydrogenase detected in cytochemical analysis of blood lymphocytes over the light microscope. The study involved 79 children and proved that in children with chronic constipation the activity of both dehydrogenases goes down, which demonstrates the apparent reduction of energy exchange of blood lymphocyte mitochondria. The correlation analysis showed that the duration of chronic constipation and the associated changes in the large intestine negatively affect the energy processes in cells. Thus the longer the pathology goes on, the smaller the energy exchange in mitochondria is resulting in reduced compensatory abilities in the body. Key words: children, chronic constipation, succinate dehydrogenase of blood lymphocytes, diagnostics.